SAFETY ANALYSIS OF NEUTRON INTERACTION WITH MATERIAL PRACTICUM MODULE FOR THE KARTINI INTERNET REACTOR LABORATORY - Prasetyo Haryo Sadewo; Puradwi Ismu Wahyono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2020)
Kartini Research Reactor, which is situated in Yogyakarta, is a 100 kW TRIGA (Training, Research, and Isotope Production by General Atomic)-type reactor mainly used for educational and training purposes. A system for remote learning on nuclear reactor physics named the Internet Rector Laboratory has been developed and is fully operational since 2019. To enrich its curriculum, a new practicum module has been developed, that can be immediately implemented and does not require any additional equipment or materials. To ensure safety in reactor kinetics and radiation protection, a safety analysis on the implementation of the practicum module has been conducted using MCNP and ORIGEN utilizing the current conditions of the reactor regarding its fuel burnup and control rod positions at a certain power level. Based on the results of the analysis, the practicum is safe to perform from a neutronic and radiation protection perspective. Given the long half-life and the large amount of radiation exposure that comes from activation products of iron, it is recommended that only cadmium, boron, graphite, and aluminum are allowed to be irradiated during the practicum.Keywords: Internet Reactor Laboratory, Activation Product, Radiation Protection, Reactor Safety